PGC-1α-Mediated Mitochondrial Quality Control: Molecular Mechanisms and Implications for Heart Failure - Chen, Lei; Qin, Yuan; Liu, Bilin; Gao, Meng; Li, Anqi; Li, Xue; Gong, Guohua (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria with structural and functional integrity are essential for maintaining mitochondrial dysfunction and cardiac homeostasis. Peroxisome proliferator-activated receptor γ coactivator 1 alpha (PGC-1α), acted as a transcriptional cofactor, is abundant in the heart, which modulates mitochondrial biogenesis and mitochondrial dynamics and mitophagy to sustain a steady-state of mitochondria. Cumulative evidence suggests that dysregulation of PGC-1α is closely related to the onset and progression of heart failure. PGC-1α deficient-mice can lead to worse cardiac function under pressure overload. Here, this review mainly focuses on what is known about the structure of PGC-1α and its regulation in mitochondrial functions, as well as its crucial role in heart failure.